The Role of Mobile Devices on Online EFL Skill Courses During Covid-19 Emergency Remote Education - Dolgunsöz, Emrah; Yıldırım, Gürkan (LPPM Universitas Advent Indonesia, 2021)
The recent Covid-19 based emergency remote education caught educational practitioners unprepared and caused learners to rely on any technology which offered them the best pedagogical solution. Since mobile devices such as smartphones, tablets, and notebooks are widely used in daily life, EFL learners also preferred to utilize them for online courses due to their undisputable mobility. However, using mobile devices in long online EFL courses is not without its limitations. This study aimed to examine the mobile experience during EFL skill courses in emergency remote education. 47 EFL preparatory class students who were attending online courses for 4 months with their mobile devices were asked to write a reflection for each skill course based on three main categories: Limitations of mobile devices, effects of mobile devices on in-classroom interaction, and device satisfaction rates. The initial findings addressed that EFL learners commonly used smartphones or notebooks for online courses rather than desktop PCs and tablets. Secondly, our results revealed various limitations for each EFL course such as limited screen size, overheating, microphone problems, and internet connection efficiency. On the other hand, although mobile devices were reported to have worked fine for in-class communication, device satisfaction rates regarding online courses were low, especially for smartphones.